Mitochondria Know No Boundaries: Mechanisms and Functions of Intercellular Mitochondrial Transfer - Torralba, Daniel; Baixauli, Francesc; Sánchez-Madrid, Francisco (Frontiers in Cell and Developmental Biology, 2016)
Mitochondria regulate multiple cell processes, including calcium signaling, apoptosis and cell metabolism. Mitochondria contain their own circular genome encoding selected subunits of the oxidative phosphorylation complexes. Recent findings reveal that, in addition to being maternally inherited, mitochondria can traverse cell boundaries and thus be horizontally transferred between cells. Although the physiological relevance of this phenomenon is still under debate, mitochondria uptake rescues mitochondrial respiration defects in recipient cells and regulates signaling, proliferation or chemotherapy resistance in vitro and in vivo. In this review, we outline the pathophysiological consequences of horizontal mitochondrial transfer and offer a perspective on the cellular and molecular mechanisms mediating their intercellular transmission, including tunneling nanotubes, extracellular vesicles, cellular fusion and GAP junctions. The physiological relevance of mitochondrial transfer and the potential therapeutic application of this exchange for treating mitochondrial-related diseases are discussed.